The DarkSide awakens. Issue 4 (May 2016) - Davini, S; Agnes, P; Agostino, L; M Albuquerque, I F; Alexander, T; Alton, A K; Arisaka, K; Back, H O; Baldin, B; Biery, K; Bonfini, G; Bossa, M; et al.
Abstract: The DarkSide program at LNGS aims to perform background-free WIMP searches using two phase liquid argon time projection chambers, with the ultimate goal of covering all parameters down to the so-called neutrino floor. One of the distinct features of the program is the use of underground argon with has a reduced content of the radioactive 39 Ar compared to atmospheric argon. The DarkSide Collaboration is currently operating the DarkSide-50 experiment, the first such WIMP detector using underground argon. Operations with underground argon indicate a suppression of 39 Ar by a factor (1.4 ± 0.2) × 10 3 relative to atmospheric argon. The new results obtained with DarkSide-50 and the plans for the next steps of the DarkSide program, the 20t fiducial mass DarkSide-20k detector and the 200 t fiducial Argo, are reviewed in this proceedings.